Knowledge Level of North Andaman Farmers towards Scientific Vegetable Cultivation Practices (Indian Journal of Extension Education, 2018)
The present study was conducted in Diglipur Tehsil of North & Middle Andaman district with 120 respondents from 8 villages using random sampling techniques during 2016-17. The results showed that 20 per cent of farming community belonged to youth and had medium level of annual income (47%). These socio-economic factors were mainly attributed to their poor adoption behaviour of cultivation practices. The vegetable cultivation significantly contributed (50%) to the farmers’ income. Further, it was found that majority of farmers still depend on private dealers to redress the pest problems. The correlation analysis with farmer’s socio-economic factors and adoption of improved cultivation practices revealed that knowledge of respondents increased with the increase in their education and income. Educating the farmers through mass media, training and demonstration will help the farmers in learning/adopting new technologies, which intern help them to increase their productivity level and their farming income on sustainable basis. Thus, it can be observed from this study that age, education and farming income influence much on motivation for learning and adoption level of farmers.